The MIREN Road Survey Database: Standardized Vegetation Sampling to Advance Our Understanding of Biodiversity Responses in Mountain Systems Across the Globe - Sylvia Haider; Jonas J. Lembrechts; Jake Alexander; Vincent Ralph Clark; Lisa J. Rew; Meike Buhaly; Marc Achermann; Alla Aleksanyan; Alisa Alvarez; Marco Andrello; José R. Arévalo; Valeria Aschero; et al. (Global Ecology and Biogeography, 2026)
Motivation The database initiated by the Mountain Invasion Research Network (MIREN) is one of the few globally implemented standardized vegetation surveys in mountains. The focus is on collecting plant species occurrences at 5‐year intervals along and adjacent to mountain roads spanning elevational gradients, with the goal of providing critical information about the ongoing spread of non‐native plants and the potential impacts of climate and human‐caused disturbance in the form of road infrastructure on mountain vegetation. Main Types of Variables Contained To date, the database contains almost 170,000 georeferenced records of plant species. Overall, 6854 vascular plant species were observed in 3364 plots across 25 regions, with many of these plots being revisited every 5 years. Each plot is identified by its coordinates, elevation and distance to the road. The status of each individual species (native, non‐native or unknown) is determined in accordance with regional databases. Spatial Location and Grain Plant species were surveyed at 20 sample sites, placed at regular elevational intervals along each mountain road, with typically three roads selected per region. Each sample site is subdivided into three 2 m × 50 m plots, one parallel to the road and two perpendicular to it, extending into adjacent vegetation. The 25 studied regions cover all continents except Antarctica. Time Period and Grain Data were collected between 2007 and 2023, with surveys being repeated at 5‐year intervals in a subset of regions. Three regions include four time‐steps, while seven and three regions were sampled three times or twice, respectively. In most regions, long‐term monitoring is ongoing. Major Taxa and Level of Measurement All vascular plant species. Software Format Data are available through a .csv file on Zenodo ( https://doi.org/10.5281/zenodo.15749536 ).

Global Analysis of Shallow Underwater Fish Observation Research: 70 Years of Progress, Persistent Geographic Biases and a Path Forward - Angus John van Wyk; Rick D. Stuart‐Smith; Jordan S. Goetze; Eva Maire; Elodie Heyns‐Veale; Kaylee Smit; Tim J. Langlois; M. Aaron MacNeil; Alejandro Pérez‐Matus; Amanda T. Lombard; Ana Carolina; Christy Semmens; et al. (Fish and Fisheries, 2026)
Marine ecosystems are increasingly threatened by overfishing, pollution, coastal development and climate change, underscoring the need for long‐term, representative information on key fish populations and habitats to inform management and policy. Underwater fish observation (UFObs) techniques, such as Underwater Visual Census (UVC), stereo‐Baited Remote Underwater Video (stereo‐BRUV) and Remotely Operated Vehicles (ROVs), play a key role in sustaining long‐term data collection. Despite technological advancements, gaps persist in understanding research focus, geographic distribution and methodological biases inherent in these methods. We conducted a scientometric analysis of 1443 peer‐reviewed publications (1953–2023), employing natural language processing and network analysis to map the research landscape. We identified 15 knowledge clusters, including marine protected areas, apex predator conservation and reef ecosystems. Our findings reveal increasing use of BRUVS and ROVs in studies of marine protected areas and subsea infrastructure, while UVC remains prevalent in shallow coral reef research. Geographic representation is skewed, with the field dominated by researchers based in Australia and the United States, and underrepresented in Africa and Southeast Asia. This imbalance highlights the need for more inclusive, globally coordinated monitoring and reporting. Our results underscore the urgency of standardising protocols within each observation method and developing interoperable reporting frameworks across techniques to maximise data comparability and foster international collaboration. Addressing these challenges will strengthen the field's capacity to inform global conservation strategies and support sustainable fisheries management.

Priorities, concerns, and potential compromises amongst urban forest stakeholders: international lessons from Aotearoa New Zealand - Thomas F. Carlin; Tim Barnard; Toby Chapman; Justin Morgenroth; Daniel R. Richards; Robyn Simcock; Jonathon Avery; Zoë Avery; Yvette Dickinson; Kate Elliot; Claire Freeman; Derek Hayes; et al. (Urban Ecosystems, 2025)
Urban forests provide numerous benefits including habitat for wildlife, improving human health, purifying air and water, and preventing and mitigating the effects of climate change. The need to protect and improve our urban forests will only increase as populations increase and cities densify and expand over time. However, urban forest establishment and maintenance is challenging due to a lack of effective policies, delays, lack of communication, inappropriate targets, and lack of recognition, disunity, or resourcing amongst stakeholders. Here we present the results from a joint urban forest symposium-workshop that sought to determine the priorities and challenges of different stakeholder groups in New Zealand, including arborists, ecologists, non-ecologist researchers, indigenous peoples, and planners. We synthesise these lessons as recommendations to improve urban forest planning, design, establishment, and minimise conflicts between stakeholder groups. While the highest priorities of each stakeholder group are fairly distinct, there are high levels of overlap in the general priorities and challenges they face in working towards advancing those priorities. We suggest a 3-phase framework to deliver progress that broadly considers (1) data collection, (2) policy development, and (3) resource development. We suggest this framework should be supported by continual monitoring and data sharing, an increased investment in green employment and education, and further recognition of urban foresters, indigenous communities, and ecologists. We suggest that an inclusive approach based on a shared understanding of forest values and removing barriers is most likely to result in long-term success.

Enabling the circular nitrogen economy with organic and organo-mineral fertilisers - Susanne Schmidt; Vithya Krishnan; Harshi Gamage; Michael Walsh; Tim Huelsen; Juliane Wolf; Peter Wadewitz; Paul Jensen; Bianca Das; Nicole Robinson (Nutrient Cycling in Agroecosystems, 2025)
The circular nutrient economy repurposes organic (formerly alive, containing organic carbon) and inorganic (mineral) recycled materials as fertilisers and soil ameliorants, and halving nitrogen (N) waste is a global goal. Our focus was unavoidable food waste and garden waste (FOGO food organics garden organics) as suitable feedstock for compost and use for cropping. We hypothesised that to realise benefits of compost, organic and organo-mineral fertilisers (OF/OMF) must be optimised for target crops and biophysical environments. We explored compost and organic recyclates (dried bacterial biomass PPB, chicken litter manure) as N sources for vegetable, fruit and grain crops in controlled experiments with single or combinations of contrasting N release and carbon-to-N ratios of 20, 13.5 (compost), 13.5 (poultry manure), 6.1 (PPB) and 0.5 (mineral N). With standardised N input (0.5–1 g N/pot and plant), compost as the sole N source resulted in less yield than all other N sources, while suitable mixtures of organic recyclates with/without added mineral N matched the yield of crops grown with mineral N. Adding 5% compost to sand growth substrate modulated crop growth and phenology, increased tillering and panicle production, or accelerated fruit ripening. This confirmed effects beyond nutrient supply, likely crop-growth modulating substances are present. Exploring effects of crop species, N source and water supply confirmed statistically significant interactions on yield, biomass and N use efficiency (NUE). This means a robust strategy for optimising OF/OMF is testing target crops with compost and recyclates to identify crop-specific responses. We recommend that applying such strategy allows manufacturers targeting N-efficient OF/OMF to service the expanding market for recyclate-based organo-mineral fertilisers and soil ameliorants for the circular N economy.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Sustainable innovation policy: Examining the discourse of UK innovation policy - Lauren Tuckerman; Jen Nelles; Kevin Walsh; Tim Vorley (Environmental Science & Policy, 2023)

Assessing Outcomes of Environmental Flows for an Estuary-Dependent Fish Species using a Novel Stochastic Population Model Approach - Daniel Stoessel; Charles R. Todd; Tim Brown; John D. Koehn; Chris Walsh; Dylan van der Meulen; Joel Williams; Melissa Birleson (Estuaries and Coasts, 2022)

Extinction risk of the endemic vascular flora of Kauai, Hawaii, based on IUCN assessments - Nina Rønsted; Seana K. Walsh; Margaret Clark; Merlin Edmonds; Tim Flynn; Scott Heintzman; Alexander Loomis; David Lorence; Uma Nagendra; Ben Nyberg; Michael Opgenorth; Lauren Weisenberger; et al. (Conservation Biology, 2022)
The International Union for Conservation of Nature's Red List of Threatened Species (IUCN Red List) is the world's most comprehensive information source on the global conservation status of species. Governmental agencies and conservation organizations increasingly rely on IUCN Red List assessments to develop conservation policies and priorities. Funding agencies use the assessments as evaluation criteria, and researchers use meta‐analysis of red‐list data to address fundamental and applied conservation science questions. However, the circa 143,000 IUCN assessments represent a fraction of the world's biodiversity and are biased in regional and organismal coverage. These biases may affect conservation priorities, funding, and uses of these data to understand global patterns. Isolated oceanic islands are characterized by high endemicity, but the unique biodiversity of many islands is experiencing high extinction rates. The archipelago of Hawaii has one of the highest levels of endemism of any floristic region; 90% of its 1367 native vascular plant taxa are classified as endemic. We used the IUCN's assessment of the complete single‐island endemic (SIE) vascular plant flora of Kauai, Hawaii, to assess the proportion and drivers of decline of threatened plants in an oceanic island setting. We compared the IUCN assessments with federal, state, and other local assessments of Kauai species or taxa of conservation concern. Finally, we conducted a preliminary assessment for all 1044 native vascular plants of Hawaii based on IUCN criterion B by estimating area of occupancy, extent of occurrence, and number of locations to determine whether the pattern found for the SIE vascular flora of Kauai is comparable to the native vascular flora of the Hawaiian Islands. We compared our results with patterns observed for assessments of other floras. According to IUCN, 256 SIE vascular plant taxa are threatened with extinction and 5% are already extinct. This is the highest extinction risk reported for any flora to date. The preliminary assessment of the native vascular flora of Hawaii showed that 72% (753 taxa) is threatened. The flora of Hawaii may be one of the world's most threatened; thus, increased and novel conservation measures in the state and on other remote oceanic islands are urgently needed.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

A probabilistic seismic hazard assessment for Wylfa Newydd, a new nuclear site in the United Kingdom - Manuela Villani; Zygmunt Lubkowski; Matthew Free; Roger M. W. Musson; Barbara Polidoro; Rory McCully; Areti Koskosidi; Crispin Oakman; Tim Courtney; Martin Walsh (Bulletin of Earthquake Engineering, 2020)

Understanding the evolving phenotype of vascular complications in telomere biology disorders - Cecilia Higgs; Yanick J. Crow; Denise M. Adams; Emmanuel Chang; Don Hayes; Utz Herbig; James N. Huang; Ryan Himes; Kunal Jajoo; F. Brad Johnson; Susan D. Reynolds; Yoshihiro Yonekawa; et al. (Angiogenesis, 2019)

Standardized reporting of the costs of management interventions for biodiversity conservation - Gwenllian D. Iacona; William J. Sutherland; Bonnie Mappin; Vanessa M. Adams; Paul R. Armsworth; Tim Coleshaw; Carly Cook; Ian Craigie; Lynn V. Dicks; James A. Fitzsimons; Jennifer McGowan; Andrew J. Plumptre; et al. (Conservation Biology, 2018)
Effective conservation management interventions must combat threats and deliver benefits at costs that can be achieved within limited budgets. Considerable effort has focused on measuring the potential benefits of conservation interventions, but explicit quantification of the financial costs of implementation is rare. Even when costs have been quantified, haphazard and inconsistent reporting means published values are difficult to interpret. This reporting deficiency hinders progress toward a collective understanding of the financial costs of management interventions across projects and thus limits the ability to identify efficient solutions to conservation problems or attract adequate funding. We devised a standardized approach to describing financial costs reported for conservation interventions. The standards call for researchers and practitioners to describe the objective and outcome, context and methods, and scale of costed interventions, and to state which categories of costs are included and the currency and date for reported costs. These standards aim to provide enough contextual information that readers and future users can interpret the cost data appropriately. We suggest these standards be adopted by major conservation organizations, conservation science institutions, and journals so that cost reporting is comparable among studies. This would support shared learning and enhance the ability to identify and perform cost‐effective conservation.

The Biaxial Biomechanical Behavior of Abdominal Aortic Aneurysm Tissue - Siobhan A. O’Leary; Donagh A. Healey; Eamon G. Kavanagh; Michael T. Walsh; Tim M. McGloughlin; Barry J. Doyle (Annals of Biomedical Engineering, 2014)

Exotic species richness and native species endemism increase the impact of exotic species on islands - Jessica C. Walsh; Oscar Venter; James E. M. Watson; Richard A. Fuller; Tim M. Blackburn; Hugh P. Possingham (Global Ecology and Biogeography, 2012)
Aim Exotic species pose one of the most significant threats to biodiversity, especially on islands. The impacts of exotic species vary in severity among islands, yet little is known about what makes some islands more susceptible than others. Here we determine which characteristics of an island influence how severely exotic species affect its native biota. Location We studied 65 islands and archipelagos from around the world, ranging from latitude 65° N to 54° S. Methods We compiled a global database of 10 island characteristics for 65 islands and determined the relative importance of each characteristic in predicting the impact of exotic species using multivariate modelling and hierarchical partitioning. We defined the impact of exotic species as the number of bird, amphibian and mammal (BAM) species listed by the International Union for Conservation of Nature (IUCN) as threatened by exotics, relative to the total number of BAM species on that island. Results We found that the impact of exotic species is more severe on islands with more exotic species and a greater proportion of native species that are endemic. Unexpectedly, the level of anthropogenic disturbance did not influence an island's susceptibility to the impacts of exotic species. Main conclusions By coupling our results with studies on the introduction and establishment of exotic species, we conclude that colonization pressure, or invasion opportunities, influences all stages of the invasion process. However, species endemism, the other important factor determining the impact of exotic species, is not known to contribute to introduction and establishment success on islands. This demonstrates that different factors correlate with the initial stages of the invasion process and the subsequent impacts of those invaders, highlighting the importance of studying the impacts of exotic species directly. Our study helps identify islands that are at risk of impact by exotics and where investment should focus on preventing further invasions.

Processes at multiple scales affect richness and similarity of non‐native plant species in mountains around the world - Tim Seipel; Christoph Kueffer; Lisa J. Rew; Curtis C. Daehler; Aníbal Pauchard; Bridgett J. Naylor; Jake M. Alexander; Peter J. Edwards; Catherine G. Parks; José Ramon Arevalo; Lohengrin A. Cavieres; Hansjörg Dietz; et al. (Global Ecology and Biogeography, 2012)
Aim To investigate how species richness and similarity of non‐native plants varies along gradients of elevation and human disturbance. Location Eight mountain regions on four continents and two oceanic islands. Methods We compared the distribution of non‐native plant species along roads in eight mountainous regions. Within each region, abundance of plant species was recorded at 41–84 sites along elevational gradients using 100‐m 2 plots located 0, 25 and 75 m from roadsides. We used mixed‐effects models to examine how local variation in species richness and similarity were affected by processes at three scales: among regions (global), along elevational gradients (regional) and with distance from the road (local). We used model selection and information criteria to choose best‐fit models of species richness along elevational gradients. We performed a hierarchical clustering of similarity to investigate human‐related factors and environmental filtering as potential drivers at the global scale. Results Species richness and similarity of non‐native plant species along elevational gradients were strongly influenced by factors operating at scales ranging from 100 m to 1000s of km. Non‐native species richness was highest in the New World regions, reflecting the effects of colonization from Europe. Similarity among regions was low and due mainly to certain Eurasian species, mostly native to temperate Europe, occurring in all New World regions. Elevation and distance from the road explained little of the variation in similarity. The elevational distribution of non‐native species richness varied, but was always greatest in the lower third of the range. In all regions, non‐native species richness declined away from roadsides. In three regions, this decline was steeper at higher elevations, and there was an interaction between distance and elevation. Main conclusions Because non‐native plant species are affected by processes operating at global, regional and local scales, a multi‐scale perspective is needed to understand their patterns of distribution. The processes involved include global dispersal, filtering along elevational gradients and differential establishment with distance from roadsides.

Impediments and Solutions to Sustainable, Watershed-Scale Urban Stormwater Management: Lessons from Australia and the United States - Allison H. Roy; Seth J. Wenger; Tim D. Fletcher; Christopher J. Walsh; Anthony R. Ladson; William D. Shuster; Hale W. Thurston; Rebekah R. Brown (Environmental Management, 2008)

On Reducing Abnormal Hemodynamics in the Femoral End-to-Side Anastomosis: The Influence of Mechanical Factors - Thomas O Brien; Michael Walsh; Tim McGloughlin (Annals of Biomedical Engineering, 2005)

The Influence of Urban Density and Drainage Infrastructure on the Concentrations and Loads of Pollutants in Small Streams - Belinda E. Hatt; Tim D. Fletcher; Christopher J. Walsh; Sally L. Taylor (Environmental Management, 2004)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)